Modele przekształceń struktur edukacyjno-zawodowych (próba weryfikacji empirycznej) - Blossfeld, Hans Peter; Szambelańczyk, Jan (Wydział Prawa i Administracji UAM, 1989)
The article presents models of social structure transformation based on qualificational changes across cohorts and career opportunities within cohorts. Taking these into account four ideal models of society were distinguished: developing by cohort, developing by cohort and expirience, developing by experience and stagnant. Using data-sets from Employee Census carried out in the Province of Poznań in 1983 and Qualificational and Occupational Career Survey in the Federal Republic of Germany from 1979 our models were subject to initial empirical verification. Firstly we compare rates of change in educational and occupational structures across cohorts (dynamic versus static societies). Secondly we analyze occupational opportunities offered to selected cohorts within the labour markets (career-open versus career-closed societies). The empirical analysis provides evidence that in more dynamic societies, such as the FRG, structural changes are rapid and organizational and technological evolution is more often accomplished by recruiting new birth cohorts of labour market entrants then by retraining older cohorts. Therefore, compared to polish data, accession to the labour force in the FRG often is found into the new and growing occupations and we thus found more intercohort changes than intracohort mobility. On the other hand, we find that in more open societies, i.e. societies with less inequality and less hierarchy, such as Poland there are more opportunities for intracohort occupational mobility and less cohort differentiation.
Models of transformations of educational and professional structures (an attempt of empirical verification).